2022
DOI: 10.1108/meq-03-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

Is agricultural development good for carbon mitigation in India? Evidence from the asymmetric NARDL model

Abstract: PurposeThe main objective of the present study is to figure out the effect of agricultural development on environmental pollution in the Indian context over the period 1970 to 2018. The study also tests the applicability of pollution haven hypothesis.Design/methodology/approachTo begin with, the authors test the stationarity of the variables by using the DF-GLS and KPSS tests. To examine the relationship between agricultural development and carbon emissions, the study applies nonlinear autoregressive distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…The existent studies have identified many social and economic factors like financial development, national income, trade, foreign direct investment (FDI), financial development, industrialization, energy consumption, and so on, as main determinants of environmental quality (Boutabba, 2014;Dar and Asif, 2018;Imamoglu, 2018;Danish et al, 2019a,b;Rasool et al, 2020;Chowdhury et al, 2021;Uzar, 2021;Zafar et al, 2023).The present study investigates the direct and the moderating role of institutional quality in the financial development and EFP nexus in the context of India.…”
Section: Financial Development Institutions Ecologymentioning
confidence: 87%
See 2 more Smart Citations
“…The existent studies have identified many social and economic factors like financial development, national income, trade, foreign direct investment (FDI), financial development, industrialization, energy consumption, and so on, as main determinants of environmental quality (Boutabba, 2014;Dar and Asif, 2018;Imamoglu, 2018;Danish et al, 2019a,b;Rasool et al, 2020;Chowdhury et al, 2021;Uzar, 2021;Zafar et al, 2023).The present study investigates the direct and the moderating role of institutional quality in the financial development and EFP nexus in the context of India.…”
Section: Financial Development Institutions Ecologymentioning
confidence: 87%
“…In terms of GDP measured in purchasing power parity ($11.33tn), the South Asia giant ranks third. India is the thirdlargest aggregate emitter of carbon dioxide accounting for 5.9% of total global emissions in 2010 after China and the United States (Zafar et al, 2023). India is also fourth-largest GHG emitter in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies attempt to investigate the dynamic relationships of different variables and their effect on environmental quality. For instance, environmental taxes (Shahzad, 2020), natural resources management (Hussain et al, 2017), green innovation (Jiakui et al, 2023), food security (Zafar et al, 2022), environmental audit (Baalouch et al, 2019). Most of the variables concerning such research studies are trade, tourism, CO 2 emission, GDP, energy consumption, FDI and FD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given this scenario, scientific community at large makes serious attempt to address the sustainability concern of the planet and trying to figure out the factors critical in mitigating the environmental problems. In this setting, several elements have been found in the economics literature explaining the economic drivers of environmental deterioration such as energy consumption, industrialization, agricultural development, transportation, urbanization, trade openness, financial development, foreign direct investment, population expansion and so on (Dar and Asif, 2018;Zafar et al, 2022;Itoo and Ali, 2023). Interestingly, studies that predicted environmental deterioration have been extensively studied using various econometric approaches and analysing different nations throughout in a different time-period.…”
Section: Introductionmentioning
confidence: 99%